Chloroplast genome of critically endangered Cotoneaster wilsonii (Rosaceae) endemic to Ulleung Island, Korea - Yang, Ji Young (Mitochondrial DNA B Resour, 2019)
Cotoneaster wilsonii Nakai is an endangered species endemic to Ulleung Island, Korea. Here we reported the first complete chloroplast gnome sequences of C. wilsonii, which is 159,999 bp in total length with the large single copy (LSC) region of 87,868 bp, the small single copy (SSC) region of 19,335 bp, and two inverted repeat (IR) regions of 26,399 bp. The plastome contains 131 genes, including 84 protein-coding, eight ribosomal RNA, and 37 transfer RNA genes. The overall GC content is 42.6% and those in the LSC, SSC, and IR regions are 34.2, 30.3, and 42.6%, respectively. Phylogenetic analysis of 21 representative plastomes within the family Rosaceae suggests strongly the monophyly of Cotoneaster and C. wilsonii being sister to the clade of Cotoneaster franchetii and Cotoneaster horizontalis.